The effect of training and development on improving of performance with competence as a mediating variable - Pangestika, Putri; Daud, Ilzar; Juniwati, Juniwati; Fauzan, Rizky; Fitriana, Ana (Enrichment : Journal of Management, 2023)
Currently, people live in a globalized environment with significant changes, especially digital technology that change how an organization provides work and the human resource management process in the organization. Generation x is experiencing significant changes in technology that affect them to adapt to the digital era. This study aims to determine the impact of training and development on improving the performance quality of Generation X employees in the West Kalimantan Provincial Government with competence as mediation. Data is presented and analyzed using quantitative methods, and the number of samples is 234 respondents. The questionnaire in this study used a five-point Likert scale (1=Strongly disagree, 2=Disagree, 3=Neutral, 4=Agree, 5=Strongly agree); the questionnaire was distributed online and offline. The analysis in this study was carried out using the Structural Equation Modeling (SEM) method through AMOS 24. The findings from this research suggest that training and development have a positive and significant effect on employee performance with intermediary competencies.